NOONAN’S SYNDROME - Zolotarova, T. V.; Maroun, B.; Hanan, S.; Mehtieva, F. B. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
The clinical case an adult patient with rare genetically heterogeneous disorder combine with congenital heart diseases and multiple stigmas of disembryogenesis, currently presenting mostly with signs of pulmonary hypertension have been reviewed. Patient is presented with definitive Noonan’s syndrome according scoring system of Van Der Burgt (has 2 major criteria). The data of the laboratory and instrumental diagnostic methods, clinical diagnosis, selection of the optimized treatment and modification of the habit of life are given. Noonan’s syndrome is a genetic disorder and prognosis for recover is an unfavorable. According to the medical literature, physicians who specialize in diagnosing and treating heart abnormalities (cardiologists) should suspect the possibility of NS in any individuals who have congenital pulmonary valve stenosis, unusual facial features and certain eye abnormalities typically found even in the more mild cases (e. g., ptosis, epicanthic folds, ocular hypertelorism.